Mosby's physical examination DVD series : DVD 15, Putting it all together: [ - Ball, Jane; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
"This 26 minute video shows but one way to put all body system examinations together in a complete assessment. It demonstrates how to combine examination techniques to minimize position changes and conserve the patient's energy. It also shows how to move roughly from head to toe and work efficiently by body region rather than by body system. In addition, it presents equipment as it is used in the complete physical examination. The video also shows how to adapt your approach to physical examination of pediatric and geriatric patients. When viewing the video, keep in mind that there is no one right way to put together the parts of a physical examination. The video is not intended to be comprehensive. Rather, it may be used as a model for the learner to develop an individual approach. The learner should evolve a process that flows smoothly for him or her and considers the patient's health history and laboratory test results."--Publisher's website